“Reclaiming Space: A Postcolonial Ecocritical Analysis of Nature and Memory in Toni Morrison’s Beloved” (London Journal of Research In Humanities and Social Sciences, 2025)
This article explores the multifaceted concept of space in Toni Morrison’s Beloved through a  postcolonial ecocritical lens, focusing on how natural and domestic spaces serve as sites of  memory, trauma, and healing for African American characters in the aftermath of slavery. The  study examines three key spaces—the Ohio River, Baby Suggs’ Clearing, and the haunted house  at 124 Bluestone Road—as symbolic realms where the characters navigate their fractured  identities and confront the lingering ghosts of their past. The Ohio River emerges as a liminal  space of rebirth and emancipation, while the Clearing represents a communal sanctuary for  spiritual and emotional healing. The haunted house, on the other hand, embodies the inescapable  past, where the trauma of slavery continues to haunt the present. Through these spaces, Morrison  not only critiques the environmental and psychological scars of colonialism but also highlights  the resilience and agency of her characters as they seek to reclaim their histories and identities.  This article argues that Morrison’s portrayal of space in Beloved underscores the  interconnectedness of human and non-human worlds, offering a profound commentary on the  enduring impact of slavery and the possibility of redemption through nature and community.
Keywords: brazil; multimorbidity; multiple long-term chronic conditions; socioeconomic positions; inequality measures; health inequalities; literature; image; Perrault; Dor; Ibarbourou; Higher education; developing countries; Educational technology; Generative AIs; curriculum; Occupational therapy; upgrade programs; competencies; diploma; educational campaigns; Youth and Adult Education; Adult Literacy; Illiteracy Legislation.; healing.; Trauma; memory; space; Toni Morrison; Beloved; postcolonial ecocriticism; Ohio River; haunted house; African American literature; slavery; environmental agency.